The association of appointment type in healthcare with patient reported experience measures: a population-based survey study - Tarja Heponiemi; Emma Kainiemi; Lotta Virtanen; Tuulikki Vehko; Anna-Mari Aalto (BMC Health Services Research)
Abstract Background Poor access to healthcare and long waiting times are severe challenges in many countries and therefore countries have increasingly adopted teleconsultations such as video, messaging, and phone calls. Patient-reported experience measures (PREMs) assess the quality of care based on patients’ insights covering topics like the quality of communication, patient participation, and adequacy of time allocation of the appointment. The present study examined whether the type of appointment (in-person, by phone call or via digital services), service sector, and encountered health professional were associated with patients’ experience of appointment quality in healthcare. Methods The data from the population-based cross-sectional Healthy Finland Survey conducted from September 2022 to February 2023 including 22 665 respondents (53% women) were used. Complex samples logistic regression analyses were used to examine the associations of the independent variables (type of appointment, the service sector and encountered healthcare professional) with PREMs (sufficient time allocation, opportunity to ask questions, active participation, and responsiveness to needs) adjusted for self-rated health, age, sex, and urbanization status. Results Those whose appointment was conducted by phone call had greater odds of not agreeing that enough time was allocated (OR = 1.57, 95%CI = 1.36–1.81), opportunity to ask was offered (OR = 1.28, 95%CI = 1.10–1.50), active participation possibilities were given (OR = 1.33, 95%CI = 1.15-1.54-), and their needs were met (OR = 1.39, 95%CI = 1.20–1.60) compared to in-person appointments. Those whose appointment was conducted by digital services had greater odds of not agreeing that enough time was allocated (OR = 1.51, 95%CI = 1.21–1.88) and opportunity to ask was offered (OR = 1.38, 95%CI = 1.07–1.78) compared to in-person appointments. Moreover, respondents had greater odds of disagreeing with PREM statements in health centers and when encountering physicians compared to their counterparts. Conclusions It seems that teleconsultations do not allocate enough time, offer opportunity to ask, give possibility to active participation, and meet patients’ needs similarly as in-person appointments. Especially appointments conducted by phone call differed negatively from in-person visits regarding all these aspects. Our findings should be kept in mind when planning and developing teleconsultations. Teleconsultations may be a good option in many cases, but not for all patients or for all situations. Moreover, physicians and health centers should adopt means to improve time allocation, patient participation, and responsiveness to patients’ needs.